WASp Deficiency Selectively Affects the TCR Diversity of Different Memory T Cell Subsets in WAS Chimeric Mice - Li, Wenyan; Jia, Yanjun; Wang, Yanping; Zhao, Qin; Yang, Lu; Zeng, Ting; Niu, Linlin; Dai, Rongxin; Li, Yanan; Zhao, Xiaodong; Wu, Junfeng (Frontiers in Immunology, 2022)
Background: The T cell receptor (TCR) diversity is essential for effective T cell immunity. Previous studies showed that TCR diversity in Wiskott-Aldrich Syndrome (WAS) patients was severely impaired, especially in the memory T cell populations. Whether this defect was caused by intrinsic WASp deficiency or extrinsic reasons is still unclear. Methods: We sorted different T cell subsets from the bone marrow chimeric mice model using both magnetic beads and flow cytometry. TCR repertoires of memory T cells, especially CD4+ effector memory T(TEM) cells and CD8+ central memory T(TCM) cells, were analyzed using the UMI quantitative high-throughput sequencing (HTS). Results: An average of 5.51 million sequencing reads of 32 samples were obtained from the Illumina sequencing platform. Bioinformatic analyses showed that compared with wild type (WT), WAS knock out (KO)-CD4+TEM cells exhibited increased Simpson index and decreased D50 index (P<0.05); The rank abundance curve of KO-CD4+TEM cells was shorter and steeper than that of WT, and the angle of qD and q in KO-CD4+TEM cells was lower than that of WT, while these indexes showed few changes between WT and KO chimeric mice in the CD8+TCM population. Therefore，it indicated that the restriction on the TCRVβ repertoires is majorly in KO-CD4+ TEM cells but not KO- CD8+ TCM cells. Principal Component Analysis (PCA), a comprehensive parameter for TCRVβ diversity, successfully segregated CD4+ TEM cells from WT and KO, but failed in CD8+TCM cells. Among the total sequences of TRB, the usage of TRBV12.2, TRBV30, TRBV31, TRBV4, TRBD1, TRBD2, TRBJ1.1 and TRBJ1.4 showed a significant difference between WT-CD4+ TEM cells and KO-CD4+TEM cells (P<0.05), while in CD8+TCM cells, only the usage of TRBV12.2 and TRBV20 showed a substantial difference between WT and KO (P<0.05). No significant differences in the hydrophobicity and sequence length of TCRVβ were found between the WT and KO groups. Conclusion: WASp deficiency selectively affected the TCR diversity of different memory T cell subsets, and it had more impact on the TCRVβ variety of CD4+TEM cells than CD8+TCM cells. Moreover, the limitation of TCRVβ diversity of CD4+ TEM cells and CD8+TCM cells in WAS was not severe but intrinsic.